2013
DOI: 10.1007/s10802-013-9822-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Social Support as Moderators of Depression, Body Image, and Disordered Eating for Suicidal Ideation in Adolescents

Abstract: The current study investigated risk factors for suicidal ideation in a community sample of 392 adolescents (males 51.9 %; females 48.1 %), while also evaluating self-esteem, perceived parent support, and perceived peer support as protective factors and potential moderators between suicidal ideation and the 3 risk factors. Disordered eating, depression, parent support, and peer support were found to be significant predictors of current suicidal ideation, but body satisfaction was not. The relationship between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 37 publications
6
47
0
3
Order By: Relevance
“…A lack of social support has been shown to have a strong association with suicidal ideation, plan and attempt (Kleiner and Greston 1982) with increased likelihood when depression and low self-esteem co-exist (Liu and Mustanski 2012; Brausch and Decker 2014). A study among pregnant adolescents found that with increased perception of support from a partner and perceived approval from parents, teenage pregnant girls reported a lower frequency of suicidal thoughts (Brown et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of social support has been shown to have a strong association with suicidal ideation, plan and attempt (Kleiner and Greston 1982) with increased likelihood when depression and low self-esteem co-exist (Liu and Mustanski 2012; Brausch and Decker 2014). A study among pregnant adolescents found that with increased perception of support from a partner and perceived approval from parents, teenage pregnant girls reported a lower frequency of suicidal thoughts (Brown et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The term social support has been previously defined as "an exchange of resources between at least two individuals perceived by the provider or recipient to be intended to enhance the well-being of the recipient" (Shumaker & Brownell, 1984, p. 13). Brausch and Decker (2014) analyzed risk factors for suicidal ideation among a community sample of 392 adolescents. Brausch and Decker (2014) analyzed risk factors for suicidal ideation among a community sample of 392 adolescents.…”
Section: Psychosocial Variables Relevant To Quality Of Lifementioning
confidence: 99%
“…The extant literature on perceived social support suggests that it mediates the links between stressful life events and psychological consequences such as anxiety, depression, and behavioral distress (Brausch & Decker, 2014;Russell & Cutrona, 1991). Results in 110 the literature have also suggested that a person's perception of the availability of others as a resource, rather than actual support received, plays an important role in the prediction of coping effectiveness, well-being, and psychological and physical health (Dolbier & Steinhardt, 2000).…”
Section: Introductionmentioning
confidence: 99%